Biological Evaluation of the Effect of Root Canal Sealers Using a Rat Model - Motoki Okamoto; Sayako Matsumoto; Kiichi Moriyama; Hailing Huang; Masakatsu Watanabe; Jiro Miura; Keita Sugiyama; Yujiro Hirose; Manabu Mizuhira; Nanako Kuriki; Julian G. Leprince; Yusuke Takahashi; et al. (MDPI AG, 2022)
Gutta-percha points and root canal sealers have been used for decades in endodontics for root canal obturation. With techniques such as single cone methods, the amount of sealer is larger, making their properties more critical. However, relatively few reports have comprehensively evaluated their biological effects. To this end, we evaluated three types of sealers, zinc oxide-fatty acid-, bio-glass- and methacrylate resin-containing sealers were considered. Their biological effects were evaluated using a rat subcutaneous implantation model. Each sealer was loaded inside a Teflon tube and implanted subcutaneously in the backs of rats. Inflammatory cells were observed around all samples 7 days after implantation and reduced after 28 days. Our results revealed that all samples were in contact with the subcutaneous tissue surrounding the sealer. Additionally, Ca and P accumulation was observed in only the bio-glass-containing sealer. Furthermore, each of the three sealers exhibited unique immune and inflammatory modulatory effects. In particular, bio-glass and methacrylate resin sealers were found to induce variable gene expression in adjacent subcutaneous tissues related to angiogenesis, wound healing, muscle tissue, and surrounding subcutaneous tissue. These results may help to understand the biological impacts of root canal sealers on surrounding biological tissues, guiding future research and comparisons with new generations of materials.